Freshwater fish diversity in an oil palm concession area in Mimika, Papua - HENDERITE L. OHEE (Biodiversitas Journal of Biological Diversity, 2016)
Ohee HL. 2016. Freshwater fish diversity in an oil palm concession area in Mimika, Papua. Biodiversitas 17: 665-672. New Guinea’s freshwater fish diversity may reach 400 species, twice the number of fish recorded in Australia. However, New Guinea’s freshwater fishes are facing rapid and poorly-planned social and economic developments, which have accelerated both habitat loss and degradation, impacting its unique biodiversity and threatening natural ecosystems. This study documents freshwater fish diversity and threats due to habitat conservation from oil palm development in the Timika Region, Papua. Fishes were sampled in canals, creeks, streams and rivers in the concession area of Pusaka Agro Lestari Company (PT. PAL) using seine and hand nets and a spear gun. Twenty two freshwater fish species in 15 families and 15 genera were recorded from the area. One of them is an endemic species ofTimika (Glossamia timika), one rainbowfish species with a restricted Southern New Guinea distribution, and 12 other native fishes. Land clearing leads to increase water turbidity and sedimentation, water temperature, and pollution which are potential threats to native fishes and their habitats. The fact that PAL’s concession is part of distribution area of known distribution of G. timika in Timika vicinity, habitat conversion to palm oil elevates the threat to this species. Hopefully, PT. PAL will adopt necessary conservation measures to mitigate the potential impact during the land clearing, especially, if they leave riparian buffer regions intact to protect aquatic habitats when clearing land.